The impact of time deposits on the rate of return on assets (Case study of the International Bank for Trade and Finance) (Journal of Hama University, 2025)
This research aims to study the impact of time deposits on the rate of return on assets (Case study of the International Bank for Trade and Finance) during the period from 2010 to 2023.The descriptive approach was adopted, as data were obtained from annual reports and financial ratios published in the Damascus Stock Exchange. The simple regression method was used to represent the relationship between the independent variable (time deposits) and the dependent  variable (rate of return on assets). To estimate the liner regression equation and test the research hypothesis, the spss statistical program was used. The statistical analysis and hypothesis testing concluded that there is a statistically significant negative impact of time deposits on the rate of return on assets (Case study of the International Bank for Trade and Finance) during the period from 2010 to 2023. This may be due to the banks reliance on the timing of these deposits and their investment in granting credit facilities. During the period studied, some facilities faltered, which made time deposits have a negative impact on the rate of return on assets.
Keywords: time deposits, rate of return on assets